The ocean response to El Nino Southern Oscillation (ENSO) in the Bali Sea: a model study. Issue 1 (1st January 2023) - Adhinugraha, F A C; Atmadipoera, A S; Hartanto, M T
Abstract: The Bali Sea (BS) is connected to the Java Sea and Makassar Strait in the north and is one of the main outflow straits of the Indonesian Throughflow (ITF) in Lombok Strait (LS). Local ocean dynamics and their variability may be controlled significantly by the ITF. This study aims to investigate the interannual variation of circulation, mixed layer depth, and isotherm of 20°C, by performing a simulation of fine- a resolution 1/84° ocean circulation model of CROCO between 2010-2020 with a focus on El Nino 2015 (EN2015) and La Nina 2020 (LN2020) events. The model validation reproduces well the satellite-derived SST and SSH dataset with a correlation coefficient of >0.9. The model demonstrated an anti-clockwise circulation of the ITF in the BS, entering via the northern and exiting into the LS via the southern area. This circulation changes drastically during the ENSO event, where the ITF transport inflow is weaker and shallower during EN2015, compared to a much stronger and deeper ITF inflow during LN2020. Accordingly, shallower mixed layer depth and depth of isotherm of 20°C are found during EN2015, and vice versa. Coherence of these parameters with NINO3.4 is very significant (>-0.89) with a phase lag of 1.7 months.